A case series of acute pericarditis following COVID-19 vaccination in the context of recent reports from Europe and the United States. Issue 45 (29th October 2021) - Lazaros, George; Anastassopoulou, Cleo; Hatziantoniou, Sophia; Kalos, Theodoros; Soulaidopoulos, Stergios; Lazarou, Emilia; Vlachopoulos, Charalambos; Vassilopoulos, Dimitrios; Tsakris, Athanasios; Tsioufis, Costas
Abstract: Background: COVID-19 vaccines were efficacious and safe in clinical trials. We report nine events of acute pericarditis (AP) in eight patients following COVID-19 vaccination with BNT162b2 (6/9), AZD1222 (2/9) and mRNA-1273 (1/9). Methods: All patients were referred for AP temporally linked with COVID-19 vaccination. Chest pain was the most common clinical manifestation. Alternative etiologies were excluded upon thorough diagnostic work up. AP diagnosis was established according to ESC guidelines. Findings: Five events occurred after the first vaccine dose and four after the second. The mean age in this cohort was 65.8 ± 10.2 years and the men/women ratio 3/5. All events resolved without sequelae; two events were complicated by cardiac tamponade requiring emergent pericardial decompression. Hospitalization was required in four cases. Interpretation: Although causality cannot be firmly established, AP has emerged as a possible complication following COVID-19 vaccination. Further investigation is indispensable to fully characterize this new entity.